Replacement of state service positions under conditions of quarantine: state and challenges - Біла-Тіунова, Любов Романівна; Біла-Тіунова, Л. Р.; Била-Тиунова, Любовь Романовна; Bila-Tiunova, Liubov R.; Bila-Tiunova, L. R.; Негара, Родіон Віталійович; Негара, Р. В.; Негара, Родион Витальевич; Nehara, Rodion V.; Nehara, R. V. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the study of ways to replace state service positions in quarantine, established to combat COVID-19. Attention is drawn to the impossibility of full-fledged replacement of state service positions as a result of the application of existing methods of replacement of state service positions (competition and transfer). The changes introduced during the quarantine in the replacement of state service positions are analyzed: suspension of the competition, suspension of the provisions of Law № 889 on competition, completion of announced competitions, appointment to state service positions by concluding a contract. In order to correct the identified problems and shortcomings in the replacement of state service positions during the quarantine period, changes and additions to current legislation are proposed. There is a need to improve the procedures for replacing state service positions that can ensure the smooth functioning of public authorities in quarantine and other similar situations.

Стаття присвячена дослідженню способів заміщення посад державної служби в умовах карантину, встановлених для боротьби з COVID-19. Звертається увага на неможливість повноцінного заміщення посад державної служби в результаті застосування існуючих методів заміщення посад державної служби (конкурс та переведення). Аналізуються зміни, внесені під час карантину у заміщенні посад державної служби: призупинення конкурсу, призупинення дії положень Закону № 889 про конкурс, завершення оголошених конкурсів, призначення на посади державної служби шляхом укладення контракту. З метою усунення виявлених проблем та недоліків у заміщення посад державної служби в період карантину пропонуються зміни та доповнення до чинного законодавства. Необхідно вдосконалити процедури заміщення посад державної служби, які можуть забезпечити безперебійну роботу органів державної влади в умовах карантину та інших подібних ситуаціях.
Bila-Tiunova L. R. Replacement of state service positions under conditions of quarantine: state and challenges / L. R. Bila-Tiunova, R. V. Nehara // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 16-33.
Keywords: state service; quarantine; replacement of state service positions; legislation; державна служба; карантин; заміщення посад державної служби; законодавство; Research Subject Categories::LAW/JURISPRUDENCE::Public law::Administrative law